SUBSTITUTION OF WATER HYACINTH IN THE DIET OF GREY MULLET Mugil cephalus (L) FRY REARED IN THE LABORATORY - SOYINKA, O. O; KUSEMIJU , K. (Nigerian Journal of Fisheries, 2011)
The effect of substituting fish feeds on the growth of Mugil cephalus fry, at various levels (20%, 30% and 40%) of dried water hyacinth, Eichhornia crassipes to reduce cost of fish production, was determined over a period of six weeks (42 days) in lagoon water condition in the laboratory. Eighty fry were used and there were four feeding regimes with a replicate for each regime, at 10 specimens per tank. The higher gain in weight of 0.39 g (125.81%) was recorded in the fry fed with 40% water hyacinth substitution diet. The higher gain in length of 1.0 cm (40.0%) was recorded in the control (100% Coppens feed). The higher condition factor was 2.59 in the 40% water hyacinth substitution diet. The better food conversion ratio, the higher food conversion efficiency and the higher specific growth rate were 2.51, 39.78% and 0.86 g/day respectively in the 40% water hyacinth diet. The economic analyses further reflected the benefit of the cost of production using 40% water hyacinth meal in M. cephalus feed for good yield and reduction in the cost of fish production.